Zoospore exudates from Phytophthora nicotianae affect immune responses in Arabidopsis. - Ping Kong; John M McDowell; Chuanxue Hong (PLoS ONE)
Zoospore exudates play important roles in promoting zoospore communication, homing and germination during plant infection by Phytophthora. However, it is not clear whether exudates affect plant immunity. Zoospore-free fluid (ZFF) and zoospores of P. nicotianae were investigated comparatively for effects on resistance of Arabidopsis thaliana Col-0 and mutants that affect signaling mediated by salicylic acid (SA) and jasmonic acid (JA): eds16 (enhanced disease susceptibility16), pad4 (phytoalexin deficient4), and npr1 (nonexpressor of pathogenesis-related genes1). Col-0 attracted more zoospores and had severe tissue damage when flooded with a zoospore suspension in ZFF. Mutants treated with ZFF alone developed disease symptoms similar to those inoculated with zoospores and requirements of EDS16 and PAD4 for plant responses to zoospores and the exudates was apparent. Zoospore and ZFFs also induced expression of the PR1 and PDF1.2 marker genes for defense regulated by SA and JA, respectively. However, ZFF affected more JA defense signaling, down regulating PR1 when SA signaling or synthesis is deficient, which may be responsible for Arabidopsis mutant plants more susceptible to infection by high concentration of P. nicotianae zoospores. These results suggest that zoospore exudates can function as virulence factors and inducers of plant immune responses during plant infection by Phytophthora.